Invited paper: modeling of nanoscale MOSFET using MATLAB - Arora, Vijay K. (Institute of Electrical and Electronics Engineers, 2009)
Quantum and high-field effects present in a nanoscale MOSFET are modeled and data processed using MATLAB. The drift response to the electric field is modeled after the intrinsic velocity that is shown to be the ultimate limit to the saturation velocity in a very high electric field. The ballistic intrinsic velocity arises from the fact that randomly oriented velocity vectors in zero electric field are streamlined and become unidirectional. The presence of a quantum emission lowers the saturation velocity. The drain carrier velocity is revealed to be smaller than the saturation velocity due to the presence of the finite electric field at the drain of a MOSFET. The velocity so obtained is considered in modeling the current-voltage characteristics of a MOSFET channel in the inversion regime and excellent agreement is obtained with the experimental data on an 80-nm channel.